Enhancing the Capacity of Certified SMEs Facilitators for the Internationalization of Aceh's Micro, Small, and Medium Enterprises - Halim, Hendra; Kesuma, T. Meldi; Siregar, M. Ridha; Faisal, Faisal; Darwanis, Darwanis; Majid, M. Shabri Abdul; Fadhil, Rahmat; A Sakir, A Sakir; Syahrizal, Teuku Muhammad; Umuri, Khairil; Sitepu, Novi Indriyani; Nurdin, Ridwan; Sari, Meutia Dwi Novita; Adam, Mulyadi; Khairi, Fitrah (Asian Journal of Community Services, 2024)
This community services aims to enhance the capabilities of certified SMEs facilitators from the Faculty of Economics and Business, Syiah Kuala University to internationalizing Aceh's Micro, Small, and Medium Enterprises (SMEs) through participation in the 19th Malaysia International Halal Showcase (MIHAS) 2023. That is not merely a journey to MIHAS; it is a strategic investment in building the competencies of facilitators who, in turn, become ambassadors of knowledge, aiding local SMEs enterprises in embracing internationalization with confidence and competence. Results showcase strengthened international networks and market reach, emphasizing the impactful role of university-community collaborations.